Investigation of electromechanical impedance and residual stress relation for samples machined by hot ultrasonic-assisted turning. (April 2022) - Sofuoğlu, Mehmet A; Haydarlar, Gökhan; Kuşhan, Melih C; Orak, Sezan; Tekkalmaz, Mesut
Electromechanical impedance (EMI) method has been widely used in recent years to evaluate the condition of structures. In this method, piezoelectric sensors are added to the structure to examine material properties. The impedance/admittance signals are recorded with the aid of the impedance analyzer without any conversion. When there is any change in structures, differences occur in these signals. Thus, changes in structures can be easily determined. It is known that residual stress plays a vital role in materials in terms of crack initiation, breakage, fatigue life, etc. In contrast, the detection of residual stress is time-consuming and it requires experience. This study reveals the effect of cutting parameters on residual stress and electromechanical impedance/admittance values. Firstly, hot ultrasonic-assisted turning was performed for Ti6Al4V material. A parametric study was carried out with different cutting depth, feed rate, and cutting speed. In the second stage, residual stress values measured by X-Ray diffraction (XRD) method and impedance/admittance values measured by an impedance analyzer were compared. In this context, empirical equations with their values between stress/impedance–admittance values have been derived. In general, it has been observed that stress values are significantly associated with impedance/admittance values and the highest correlation was obtained with the reactance values.